Convergent Evolution of Endosymbiont Differentiation in Dalbergioid and Inverted Repeat-Lacking Clade Legumes Mediated by Nodule-Specific Cysteine-Rich Peptides. Issue 2 (18th August 2015) - Czernic, Pierre; Gully, Djamel; Cartieaux, Fabienne; Moulin, Lionel; Guefrachi, Ibtissem; Patrel, Delphine; Pierre, Olivier; Fardoux, Joël; Chaintreuil, Clémence; Nguyen, Phuong; Gressent, Frédéric; Da Silva, Corinne; et al.
Abstract : Several species from an ancient legume lineage independently evolved a novel class of cysteine-rich peptides to impose a differentiation process on their endosymbionts. Abstract: Nutritional symbiotic interactions require the housing of large numbers of microbial symbionts, which produce essential compounds for the growth of the host. In the legume-rhizobium nitrogen-fixing symbiosis, thousands of rhizobium microsymbionts, called bacteroids, are confined intracellularly within highly specialized symbiotic host cells. In Inverted Repeat-Lacking Clade (IRLC ) legumes such as Medicago spp., the bacteroids are kept under control by an arsenal of nodule-specific cysteine-rich (NCR ) peptides, which induce the bacteria in an irreversible, strongly elongated, and polyploid state. Here, we show that in Aeschynomene spp. legumes belonging to the more ancient Dalbergioid lineage, bacteroids are elongated or spherical depending on the Aeschynomene spp. and that these bacteroids are terminally differentiated and polyploid, similar to bacteroids in IRLC legumes. Transcriptome, in situ hybridization, and proteome analyses demonstrated that the symbiotic cells in the Aeschynomene spp. nodules produce a large diversity of NCR -like peptides, which are transported to the bacteroids. Blocking NCR transport by RNA interference-mediated inactivation of the secretory pathway inhibits bacteroid differentiation. Together, our results support the view that bacteroid differentiation in the Dalbergioid clade, which likely evolved independently from the bacteroid differentiation in the IRLC clade, is based on very similar mechanisms used by IRLC legumes.